The surgical treatment of unstable distal radius fractures by angle stable implants: a multicenter prospective study - Matschke, Stefan; Marent-Huber, Marta; Audigé, Laurent; Wentzensen, Andreas (Journal of orthopaedic trauma, 2011)
Objectives: - The goal of this study is to document the 2-year outcome after surgical treatment of distal radius fractures using an angle stable implant. - Design: - Prospective case-series. - Setting: - Multicenter study in nine trauma units with recruitment between December 2001 and May 2003. - Patients: - One hundred eight patients with the same number of distal radius fractures. - Intervention: - Open reduction and internal fixation with the LCP DR 3.5 mm (Synthes GmbH, Oberdorf, Switzerland). - Main Outcome Measurements: - Disabilities of the Arm, Shoulder and Hand, Gartland and Werley, SF-36 scores, radiologic assessment, and return to work status at 2 years. - Results: - At 2 years, the mean range of motion (relative to the contralateral wrist) was 83% for palmar flexion, 91% for extension, 94% for radial deviation, 92% for ulnar deviation, and 98%/94% for pronation/supination angles. Grip strength was 90% of the mean uninjured side. The average radiographic measurements were 23.6° for radial inclination angle, 6.1° for palmar (volar) tilt angle, and 0 mm for ulnar variance. The proportion of fractures for which the Gartland and Werley score was categorized as either good or excellent was 89%. Minor complications occurred in 14 patients, although none of these events were considered to be directly related to the implant. - Conclusion: - After a 2-year follow-up period, the use of an angle stable implant for unstable distal radius fractures provides adequate fixation with minimal loss of reduction. This device is associated with good functional and radiologic outcome for the patient and is indicated for distal radius fractures classified as Orthopaedic Trauma Association (OTA) Type 23-A2/A3, OTA Type 23-B2/B3, and OTA Type 23-C.